Disease activity in systemic lupus erythematosus related to a range of antibodies binding DNA and synthetic polynucleotides. Issue 9 (September 1988) - Isenberg, D A; Dudeney, C; Williams, W; Todd-Pokropek, A; Stollar, B D
Abstract : Antibodies to dDNA, nDNA, Z-DNA, poly(dT), poly(I), poly(dG.dC), poly(dA.dT), and total IgG and IgM were measured in five serial bleeds from 39 patients with systemic lupus erythematosus (SLE). The main findings were that those patients with renal disease form a distinct subset whose antibody levels correlate well with disease activity; anti-poly(dT) antibodies showed the best overall correlation with disease activity; and discriminant functional analysis demonstrated a major improvement in correlation of disease activity with combinations of antibodies to dDNA/nDNA/Z-DNA/poly(dT) (generally 50% or more were correctly classified) than with dDNA or nDNA alone (generally less than 25% correct). Serum IgG (but not IgM) correlated significantly (p less than 0.01) with six antibodies, suggesting that polyclonal activation plays a part in the development of these antibodies, though antibody cross reactivity is not excluded.